2017
DOI: 10.1021/acs.nanolett.6b04821
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of Topologically-Protected Supercooled Skyrmions in a Thin Plate of Chiral Magnet Co8Zn8Mn4

Abstract: Magnetic skyrmions in CoZnMn thin plates are observed to deform in a metastable state prepared in a magnetic-field-cooling process by way of the thermal-equilibrium skyrmion phase. In cooling, the disk-shape skyrmions change to bar- or L-shaped elongated form, whereas the skyrmion density is nearly conserved. The deformation of the skyrmions in the supercooled metastable phase is observed irrespective of the crystallographic orientation of the thin plate, whereas the elongation direction nearly aligns along th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 30 publications
1
40
0
Order By: Relevance
“…We observe two types of elliptical skyrmions with opposite chirality and different elongation directions, which are tied to the crystal's high symmetry directions. The ellipticity is therefore an intrinsic property of materials with D 2d symmetry, in contrast to the recently observed distorted skyrmions in confined B20 materials [23][24][25][26][27][28] . The formation of two distinct chiral spin textures with opposite topological charges of ±1 in one material system makes the D 2d and related systems especially fascinating.…”
mentioning
confidence: 73%
“…We observe two types of elliptical skyrmions with opposite chirality and different elongation directions, which are tied to the crystal's high symmetry directions. The ellipticity is therefore an intrinsic property of materials with D 2d symmetry, in contrast to the recently observed distorted skyrmions in confined B20 materials [23][24][25][26][27][28] . The formation of two distinct chiral spin textures with opposite topological charges of ±1 in one material system makes the D 2d and related systems especially fascinating.…”
mentioning
confidence: 73%
“…Co10Zn10, one end-member of a solid solution (Co0.5Zn0.5)20-xMnx (0 ≤ x ≤ 20) with the β-Mn structure (16), shows a helical ordering of Co spins (periodicity λ ~ 185 nm) below Tc ~ 460 K, with Tc decreasing as the partial substitution of Mn proceeds. In Co8Zn8Mn4 (Tc ~ 300 K), a SkX state created close to Tc can persist as a metastable state over a very wide temperature and magnetic field region upon a field cooling (FC), accompanied by a latticeform transformation of the SkX at low temperatures (17,18). The other end-member Mn20 (β-Mn itself) is well-known to display no transition to magnetic long range order (19,20) due to the strong geometrical frustration of antiferromagnetic interactions in the threedimensional hyper-kagome network of the 12d sites (21).…”
Section: Introductionmentioning
confidence: 99%
“…In a number of materials it has been observed that the equilibrium skyrmion region is stable over a significantly wider temperature range in thin films than in bulk crystals [7,9,[29][30][31]. One intriguing example of these materials is Cu 2 OSeO 3 , which is a multiferroic insulator that hosts magnetic skyrmions in a phase diagram that is qualitatively very similar to that of MnSi.…”
Section: Introductionmentioning
confidence: 99%